(untitled) (Research, Society and Development, 2022)
There are three categories of free roaming dogs: those with an owner, community dogs and abandoned dogs. These free-roaming dogs are vulnerable to animal cruelty and can cause traffic accidents and affect human health through transmission of zoonoses and bite injuries. The physical and ownership status of these dogs is unknown in most cities. The objective of this study was to report findings of physical evaluation and determine the ownership status of free roaming dogs in the municipality of Campo Magro, Paraná, Brazil. Whilst surveying stay dog populations to estimate numbers, observational physical assessment and interviews with passersby about the ownership of the animals were conducted. Of the 240 dogs counted, 46.7% (112/240) were classified as “dog with owner, 29.2% (70/240) as “community dog” and 24.2% (58/240) as “abandoned dog”; 63.8% (153/240) were male, 22.9% (35/153) were neutered. Most animals (75.4%; 181/240) had an ideal body score, but lower body condition scores were found in community and abandoned dogs (p <0.05). Abandoned animals had significantly more skin nodules (p<0.05) and higher prevalence of pruritus was observed in community dogs (p<0.05). These results demonstrate the need for a population management program for dogs which includes strategies for reproductive control, animal health care and promotion of responsible guardianship.